2018
DOI: 10.3389/fevo.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into the Genetic Basis of Blueberry Fruit-Related Traits Using Diploid and Polyploid Models in a GWAS Context

Abstract: Polyploidization is an ancient and recurrent process in plant evolution, impacting the diversification of natural populations and plant breeding strategies. Polyploidization occurs in many important crops; however, its effects on inheritance of many agronomic traits are still poorly understood compared with diploid species. Higher levels of allelic dosage or more complex interactions between alleles could affect the phenotype expression. Hence, the present study aimed to dissect the genetic basis of fruit-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 92 publications
8
96
0
Order By: Relevance
“…After filtering a total of 85,973 SNP were used in the GS analysis. Further information regarding population composition and genotyping approach were described in Ferrão et al (2018). The genotypes for the diploid calling were coded as 0 ( AA ), 1 ( AB ), or 2 ( BB ).…”
Section: Methodsmentioning
confidence: 99%
“…After filtering a total of 85,973 SNP were used in the GS analysis. Further information regarding population composition and genotyping approach were described in Ferrão et al (2018). The genotypes for the diploid calling were coded as 0 ( AA ), 1 ( AB ), or 2 ( BB ).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the genetic studies in polyploid species simplify the data to use diploid models inducing errors as under‐ or overestimating the real genetic control of important traits (Dufresne et al, 2014), as observed in the autotetraploid blueberry (Ferrão et al, 2018) and in the allotetraploid clover (Inostroza et al, 2018). However, Urochloa spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the consequences of using these models on the GWAS results compared with the use of adequate allele dosage, especially considering Urochloa spp. Ferrão et al (2018) performing GWAS analysis in autotetraploid blueberries ( Vaccinium corymbosum L.) verified that the importance of tetraploid models varies with traits and the use of diploid models has hindered the detection of single nucleotide polymorphism (SNP)–trait associations in this autotetraploid species. In turn, Inostroza et al (2018) only detected significant SNP–trait association in the allotetraploid clover ( Trifolium repens L.) when GWAS analyses were performed with tetraploid genetic models, showing the importance of considering the correct allele dosage.…”
mentioning
confidence: 99%
“…Firmness is a genetically controlled trait that has long been among the focus of blueberry breeding programs (Edwards et al, 1974; Cappai et al, 2018; Cellon et al, 2018; Ferrão et al, 2018). It is also a desirable trait across the whole market chain: for growers, less fruit is discarded due to physical damage; for retailers, firmer berries have a longer shelf life; and for consumers, firm texture positively correlates to liking (Mehra et al, 2013; Olmstead and Finn, 2014; Yu et al, 2014; Gilbert et al, 2015).…”
Section: Introductionmentioning
confidence: 99%